Becoming a scholarly management practitioner – Entanglements between the worlds of practice and scholarship. Issue 2 (July 2021) - Rigg, Clare; Ellwood, Paul; Anderson, Lisa
Abstract: Our contribution in this paper is to elucidate how doctoral education can enable professionals to develop through an experiential pedagogy that is based on a theoretical model of scholarly management practice. It will draw from our experience of designing and running a large online DBA with participants from across the world. We present a model of Scholarly Management Practice and explain how its use differentiates this approach to doctoral education from others in that there is a clear focus on how holders of the DBA enact their management practice, characterized by an orientation to problematization, inquiry, dialogue and critical reflection. We describe the design and underlying theoretical and philosophical rationale for how the program elements articulate together to stimulate the development of scholarly management practitioners. The implications for teaching and learning are presented in the form of a description and rationale for the design of the program in its three stages. We illustrate the trajectory of potential development as a doctoral practitioner through the vignette of one student's journey. We also reflect on the limitations and lessons learned of our own theorising and practice in the development and delivery of this DBA. Highlights: Scholarly practice strengthens reflexivity in managers in order to deal with ambiguity and complexity. The Liverpool Model of Scholarly Management Practice comprises inquiry, critical reflection and collaborative dialogue. This DBA design is characterized by praxis and phronesis and predicated on an epistemology of practice. Development of scholarly practice requires a philosophy of knowledge that makes explicit the iterative entanglement of practice and knowledge.